Hybrid Model to Assess the Readiness of Information Technology Implementation in Islamic Banking Based - Khaerul, Manaf; S.W, Pitara; Beki, Subaeki; Faiz, M. Kaffah; Cecep Nurul, Alam; Aedah, Abd Rahman (2020)
Based Indonesia's economy is driven by micro and community-based community segments. To support the development of the sharia economy very rapidly, Islamic banking needs to be equipped with an integrated system before the latest information technology. Through e-banking banks and clients can be mutually beneficial, this has become a necessity in thebanking industry today. Utilization of Information Systems is still problematic with problems between organizations of the organization's business processes. The main objective of this research is to propose a financial model for Islamic banking, a model that supports several levels, which aims to achieve factors and customers, with possible values. Through a truly systematic viewpoint, e-readiness is a concept that encompasses the environment, processes and output phases of the Islamic banking system facilitated by internet users. An assessment model that includes all information and information about e-readiness is one of the benefits of the proposed model, including features at the national and regional levels in providing better opportunities for banks in e-banking development